Stability of nonaxisymmetric ferrofluid flow in rotating cylinders with magnetic field - Jitender Singh; Renu Bajaj (International Journal of Mathematics and Mathematical Sciences)
Effect of an axially applied magnetic field on the stability of a ferrofluid flow in an annular space between two coaxially rotating cylinders with nonaxisymmetric disturbances has been investigated numerically. The critical value of the ratio Ω∗ of angular speeds of the two cylinders, at the onset of the first nonaxisymmetric mode of disturbance, has been observed to be affected by the applied magnetic field.